2018
DOI: 10.1519/jsc.0000000000001636
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Demands of the Hang Power Clean and Jump Shrug: A Joint-Level Perspective

Abstract: Kipp, K, Malloy, PJ, Smith, J, Giordanelli, MD, Kiely, MT, Geiser, CF, and Suchomel, TJ. Mechanical demands of the hang power clean and jump shrug: a joint-level perspective. J Strength Cond Res 32(2): 466-474, 2018-The purpose of this study was to investigate the joint- and load-dependent changes in the mechanical demands of the lower extremity joints during the hang power clean (HPC) and the jump shrug (JS). Fifteen male lacrosse players were recruited from a National Collegiate Athletic Association DI team,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 19 publications
8
45
0
Order By: Relevance
“…Research investigating the optimal load for weightlifting pulling derivatives is limited because of the lack of criteria that indicates a successful repetition (100). However, several studies have suggested that lighter loads (i.e., 30-45% 1RM hang power clean) may optimize training stimuli for the jump shrug (60,92,(102)(103)(104)(105) and hang high pull (94,102,104) 33-35,73) may produce the optimal training stimulus for velocity and power adaptations during the clean/snatch pull from the floor. Practitioners should however consider that the optimal load for power production may be specific to the joint, athlete plus load system, or the bar (66), may be altered based on the relative strength of the athlete (87), and may be impacted by movement pattern and the fatigue status of the athlete Strength and Conditioning Journal | www.nsca-scj.com (54).…”
Section: Speed-strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…Research investigating the optimal load for weightlifting pulling derivatives is limited because of the lack of criteria that indicates a successful repetition (100). However, several studies have suggested that lighter loads (i.e., 30-45% 1RM hang power clean) may optimize training stimuli for the jump shrug (60,92,(102)(103)(104)(105) and hang high pull (94,102,104) 33-35,73) may produce the optimal training stimulus for velocity and power adaptations during the clean/snatch pull from the floor. Practitioners should however consider that the optimal load for power production may be specific to the joint, athlete plus load system, or the bar (66), may be altered based on the relative strength of the athlete (87), and may be impacted by movement pattern and the fatigue status of the athlete Strength and Conditioning Journal | www.nsca-scj.com (54).…”
Section: Speed-strengthmentioning
confidence: 99%
“…Although previous research supports the notion that weightlifting catching derivatives may train an athlete's ability to "absorb" a load during impact activities (68), more recent studies indicate that weightlifting pulling derivatives that exclude the catch phase may produce a similar or greater load absorption stimulus (i.e., loading work, mean force, and duration) following the second pull compared with weightlifting catching derivatives (17,99). Moreover, further research has demonstrated that weightlifting pulling derivatives produce comparable (11,12) or greater (60,102,104,105) force, velocity, and power characteristics during the second pull compared with weightlifting movements that include a catch element. Although the complete removal of weightlifting catching derivatives is not being suggested, the integration of weightlifting pulling derivatives into resistance training programs should be considered for the comprehensive development of an athlete's forcevelocity profile, as elimination of the catch phase permits the use of greater loads (i.e., greater forces) (14,16,39) and potentially greater velocities (95,101).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, power production was higher in the MTP from 30-70% BM when compared to HPC, but at 80-90% BM this shifted toward HPC prevalence over MTP. As stated before, there are several factors such as rate of force development (6), impulse (6,23), propulsion (34) and joint internal power output (20) that contribute to effective levels of power production. That reinforces the idea of prescribing not only the exercises that work the same musculature/joints but also the ones that are more similar in nature with sport-specific moves, so the athlete can enhance performance more effectively.…”
Section: Optimal Load Based On Bm In Different Weightlifting Derivativesmentioning
confidence: 99%
“…Consequently, the strategy that has largely been used to determine the training load for these exercises is using percentages of the PC or HPC (6,27,33). However, the application of this method requires the individual to become very proficient in a more complex exercise to determine the training load of less complex exercises (5,20,34).…”
Section: Introductionmentioning
confidence: 99%